The effects of dual anti-platelet therapy on titanium implant osseointegration: an experimental study - Kobat, Mehmet Ali; Dündar, Serkan; Bozoglan, Alihan; Gelen, Mehmet Ali; Kıvrak, Tarik; Artaş, Gökhan; Aydin, Suna (My University, 2022)
Aim: In this study, we aim to investigate the effect of dual anti-platelet agents on osseointegration by studying a sample of rats with titanium implants in their tibias. Material and Method: The titanium implants were placed surgically to the left tibias of a sample group of 50 rats. After implantation, the rats were randomly divided into five groups: acetylsalicylic acid (ASA) (n =10), treated with 20 mg/kg of ASA; ASA+ clopidogrel (CLPD) (n=10), treated with 20 mg/kg of ASA and 30 mg/kg of CLPD; ASA+ prasugrel (PRSG) (n=10), treated with 20 mg/kg of ASA and 15 mg/kg of PRSG; ASA+ ticagrelor (TCGR) (n=10), treated with 20 mg/kg of ASA and 300 mg/kg of TCGR; and a control group (CNT) (n =10) received no further treatment following implant surgery. The experimental period lasted four weeks, during which all medications were administered with oral gavage. Concluding the experimental period, the animals were euthanized, and researchers collected blood serums and the implants, along with some surrounding bones, from each rats. Results: Bone implant connection and bone filling ratios (%) were observed histologically and documented. The bone-implant connection and bone filling ratios of the rats do not show statistically significant differences between the groups examined (P>0.05). Conclusion: In this study, it was shown that there was no bone healing problem between the antiaggregant given groups and between these groups and the control group. Too many people have to take single or double antiaggregant due to many diseases. We think that it is an important study in terms of knowing that bone healing will not be negatively affected when dental implants or other bone prosthesis procedures are applied to these patients. The results of this study should be supported by further research.
Keywords: Anti-platelet drugs; bone healing; bone-implant connection; dental implant osseointegration; dual antiplatelet theraphy